Literacy Activity to Explore Students' Habit in the Classroom - Meutia, Cut Intan (the Study Program of Education for Islamic Elementary School Teachers (Undergraduate), 2021)
This study discussed the application of the basic school literacy activity. The purpose of this was to contribute to improving the reading and writing skills of elementary school students. In addition, it aimed to solve the difficulties faced by the school in implementing the school literacy movement. This applied research was conducted for fifteen minutes each day for a period of one month. As participants, there were low-grade students, namely grade one and high-class students which was grade five. The first-grade students numbered about thirty as well as the fifth grade. The research instrument used observation, documentation study and interviews. The results showed that schools have not been able to implement the school literacy movement based on existing provisions. This can be seen from a number of inadequate facilities and the readiness of the teachers as well the students who were difficult to involved in the activity.